Hubungan Motivasi Belajar Daring pada Siswa Sekolah Menengah Melalui Pola Konsumsi Media sosial TikTok Sebagai Pembelajaran Alternatif - Herma Retno Prabayanti; Kartika Rinakit Adhe; Yahya Ramadoni (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The availability of a number of social media applications provides easy access for everyone to interact, especially the student segment as part of Generation Z. The social media application TikTok is one of the popular media for sharing short videos from handheld devices. Based on data quoted from Key Market Indicators (KMI) (Dagendart, 2021), the number of TikTok application users in Indonesia has increased significantly from year to year. Due to the COVID-19 pandemic, online learning is still the main learning model. Certain innovations should be noted so that online learning is more interactive and does not reduce students’ motivation to absorb the subject matter. TikTok is here to answer the needs of these students in the era of the COVID-19 pandemic. By using correlational quantitative methods, researchers can find out the relationship between media usage patterns of high school students who use TikTok media to carry out alternative learning. It is known that there is a positive relationship between the pattern of middle school TikTok media use and motivation to learn. If the author is able to find a certain relationship between high school students and the alternative learning media based on TikTok video, it will be able to provide a new discourse in the concept of independent learning.